Association between sedentary behavior and bone mass in adolescents - Klen J.A.* (2020)
© 2020, International Osteoporosis Foundation and National Osteoporosis Foundation.Summary: The effects of sedentary behavior on adolescents’ bone health are controversial because, even in normal weight individuals, the excessive time spent in some specific types of these behaviors appears to have no negative effect on bone health. Purpose: To analyze the relationship between sedentary behaviors and bone mass in adolescents. Methods: One hundred four adolescent boys and girls, aged 10 to 14 years, were divided into normal weight and overweight according to weight status. Specific sedentary behaviors (time spent on the Internet for school and non-school purposes, using the computer, watching television, and playing videogames) were assessed by questionnaire, and the total sedentary behavior time by accelerometry. Bone parameters were collected using X-ray absorptiometry, using total and lumbar bone mineral density (BMD) and total and lumbar bone mineral content (BMC) values. Results: In both groups, the time spent on the Internet for non-school purposes was positively correlated to the total and lumbar BMD. Also, while in the overweight group, the time spent using the computer was negatively correlated to lumbar BMD, and the time spent on the Internet for non-school purposes was positively correlated to the total and lumbar BMC, and in the normal weight group, the time spent on the Internet for non-school purposes was positively correlated to lumbar BMC. Conclusions: Adolescents who spend more time in sedentary behavior, especially using the Internet for non-school purposes, have higher BMD and BMC, while normal weight adolescents who spend more time on the computer have lower BMD.